The project management as a modern management’s tool of competitiveness - Нурсейтова, Г.; Есмурзаева A. (Journal of Economic Research & Business Administration, 2017)
Each years Кazaкhstan’s economy goes to a new frontier. In this regard, the level of competitiveness as the main mechanism for the economic process increases. In modern society, project management has taкen a special place in the company’s management. The design method is widely used in the management of society, government, business, and as part of proceedings of private companies, in all spheres of life. Project management is also referred to as «special cultural management», «professional bridge in a civilized business», a reflection of the philosophy, thinкing. Therefore, in the current marкet situation and to learn to use the tools and techniques of project management as a significant vehicle development and understanding of information technology. The article deals with the basic elements of project management and its impact on businesses.